The mixed capacitated general routing problem under uncertainty - Beraldi, Patrizia; Bruni, Maria Elena; Laganà, Demetrio; Musmanno, Roberto (European journal of operational research, 2015)
•Probabilistically constrained formulation.•Deterministic formulation where uncertain parameters follow a normal distribution.•Branch-and-cut algorithm and an efficient heuristic algorithm. We study the General Routing Problem defined on a mixed graph and with stochastic demands. The problem under investigation is aimed at finding the minimum cost set of routes to satisfy a set of clients whose demand is not deterministically known. Since each vehicle has a limited capacity, the demand uncertainty occurring at some clients affects the satisfaction of the capacity constraints, that, hence, become stochastic. The contribution of this paper is twofold: firstly we present a chance-constrained integer programming formulation of the problem for which a deterministic equivalent is derived. The introduction of uncertainty into the problem poses severe computational challenges addressed by the design of a branch-and-cut algorithm, for the exact solution of limited size instances, and of a heuristic solution approach exploring promising parts of the search space. The effectiveness of the solution approaches is shown on a probabilistically constrained version of the benchmark instances proposed in the literature for the mixed capacitated general routing problem.